Strategy of skull base reconstruction after endoscopic transnasal pituitary adenoma resection - Zhang, Chao; Yang, Zhijun; Liu, Pinan (Frontiers in Surgery, 2023)
Objective Endoscopic endonasal surgery (EES) is commonly performed for resection of lesions of the anterior/middle cranial fossa region. Cerebrospinal fluid (CSF) leakage is a major complication. Skull base reconstruction after EES is challenging. We describe our reconstruction strategy and technique and analyze its outcomes. Methods We retrospectively analyzed 703 patients with pituitary adenoma who underwent EES in our center from January 2020 to August 2022. Clinical, imaging, operative, and pathologic data were recorded from the medical records and analyzed. Skull base reconstruction was performed to achieve the following three goals: seal the original leak, eliminate dead space, provide blood supply, and early ambulation. Reconstruction was tailored to individual patients based on grade of CSF leakage encountered during surgery. Results The number of patients with a grade 0, 1, 2, and 3 intraoperative CSF leak was 487, 101, 86, and 29, respectively. Overall incidence of postoperative CSF leakage was 0.14% (1/703). Fascia sutured and vascularized nasoseptal flap were selected for all grade 3 CSF leaks. One patient who experienced postoperative CSF leakage developed intracranial infection and were treated with lumbar CSF drainage that failed; eventually re-exploration surgery for repair was required. Other patients did not have complications such as CSF leak and infection. 29 patients with grade 3 CSF leakage did not complain of severe nasal complications after operation. No perioperative complications related to the strategy (overpacking, infections, or hematomas) occurred. Incidence of postoperative CSF leak according to intraoperative leak grade was as follows: grade 0, zero; grade 1, zero; grade 2, 1.16% (1/86); and grade 3, zero. Conclusion The principles of sealing the original leak, eliminating dead space, providing blood supply, and early ambulation are key in skull base reconstruction after EES. Individualization of these principles can significantly reduce the incidence of postoperative CSF leakage and intracranial infection and reduce the use of lumbar CSF drainage. Skull base suture technique is safe and effective in patients with high-flow cerebrospinal fluid leaks.